The Relationship Between Human Resource Planning and Operational Effectiveness in National Private Companies - Joanico Sarmento Gomes; Pudji Astuty (PT. ALHAFI BERKAH INDONESIA, 2025)
This study analyzes the relationship between human resource planning and operational effectiveness in national private companies. A quantitative method with survey approach was used to collect data from 150 managers across 30 national private companies in Jakarta, Surabaya, and Bandung. The research instrument consisted of structured questionnaires using a 5-point Likert scale. Multiple linear regression analysis revealed a significant positive correlation (r = 0.742, p < 0.01) between HR planning and operational effectiveness. HR planning variables explained 55.1% of the variance in operational effectiveness. Workforce planning dimension contributed most significantly (β = 0.453) to operational effectiveness. Findings indicate that companies with good HR planning systems experienced an average productivity increase of 23.5% and employee turnover reduction of 18.3%. This research contributes theoretically to HRM field and practically for corporate policy makers in enhancing operational effectiveness through optimal HR planning.